find (a-b)-c when a=5/9,b=2/3,c=3/2
Answers
Answered by
0
Answer:
a=5/9 b=2/3 c=3/2
Step-by-step explanation:
step 1 : (a-b)-c (first we should substitute values)
step 2: (5/9-2/3)-3/2 (solve first inside brackets)
step 3: (5*3-2*1/9)-3/2 (taking lcm)
step 4: (15-2/9)-3/2 (remove brackets )
step 5: 13/9-3/2 (take lcm)
step 6: 13*2-3*9/9*2
step 7: 26-27/18
step 8: -1/18 answer
add this answe as brainlist
Similar questions
English,
6 months ago
Social Sciences,
6 months ago
Computer Science,
6 months ago
Math,
1 year ago
Science,
1 year ago